Comparative analysis of the Polycyclic Aromatic Hydrocarbons’ content (PHAs) in two separate rice husk forms in Iraq - A.Abdul, Dalia; A.Omar, Trifa (Sulaimani Journal for Pure and Applied Sciences, 2021)
Polycyclic aromatic hydrocarbons (PAHs) are harmful compositions developed typically for thermal applications in the atmosphere or amid the pyrolysis of organic fuels. The goal of this research is to compare the polycyclic aromatic hydrocarbons’ content (PAHs) in two rice husk’s distinctive sorts in southern and northern Iraq via switched phase high-achievement fluid activity utilizing UV and fluorescence detection. Seven species of polyaromatic hydrocarbons (PAHs) in rice husk of (north Iraq) were determined with the concentration: naphthalene (38.6×10-3), acenaphthylene (46×10-3), acenaphthene (98.8×10-3), benzo (a) anthracene (25.22×10-3), benzo (k) fluoranthene (141.88×10-3), benzo(g.h,i) perylene (7.62×10-3), indeno (1,2,3cd) pyrene (46.2×10-3), while Arabian rice husk (south Iraq) contain six species of PAHs with a different concentration, acenaphthylene (84.04×10-3), acenaphthylene (59.8×10-3), benzo (a) anthracene (104.38×10-3), benzo (k) fluoranthene (136.4×10-3), benzo (g.h,i) perylene (7.62×10-3), indeno (1,2,3cd) pyrene (46.2×10-3), highest PAH concentration in two types of rice husk was benzo (k) fluoranthene ,while lowest concentration PAH was benzo (g.h,i) perylene.
Keywords: polycyclic Aromatic Hydrocarbons(PAHs); HPL; rice husk